Thresholds for optimal fluid administration and weight gain after laparoscopic colorectal surgery. Issue 4 (2nd April 2019) - Hübner, M; Pache, B; Solà, J; Blanc, C; Hahnloser, D; Demartines, N; Grass, F
Abstract: Background: Perioperative fluid overload is an important modifiable risk factor for adverse outcomes after colorectal surgery. This study aimed to define critical thresholds for perioperative fluid management and postoperative weight gain for patients undergoing elective laparoscopic colorectal surgery. Methods: This was an analysis of consecutive elective laparoscopic colorectal resections at Lausanne University Hospital from May 2011 to May 2017. Main outcomes were overall, major (Clavien–Dindo grade IIIb or above) and respiratory complications, and postoperative ileus. Thresholds regarding perioperative fluid management and postoperative weight gain were identified through receiver operating characteristic (ROC) analysis and clinical judgement. Independent risk factors for all four outcomes were assessed by multinominal logistic regression. Results: Overall and major complications occurred in 210 (36·2 per cent) and 46 (7·9 per cent) of 580 patients respectively. Twenty-three patients (4·0 per cent) had respiratory complications and 98 (16·9 per cent) had postoperative ileus. Median length of hospital stay was 5 (i.q.r. 3–9) days. Based on respiratory complications, thresholds for perioperative intravenous fluid administration (postoperative day (POD) 0) were set pragmatically at 3000 ml for colonic (calculated threshold 3120 ml (area under ROC curve (AUROC) 0·63)) and 4000 ml for rectal (AUROC 0·79) procedures. Postoperative weight gain of 2·5 kg at POD 2 was predictive of respiratory complications. Multivariable analysis retained perioperative intravenous fluid administration over the above thresholds as an independent risk factor for overall (odds ratio (OR) 2·25, 95 per cent c.i. 1·23 to 4·11), major (OR 2·49, 1·17 to 5·31) and respiratory (OR 4·71, 1·42 to 15·58) complications. Weight gain above 2·5 kg at POD 2 was identified as a risk factor for respiratory complications (OR 3·58, 1·10 to 11·70) and ileus (OR 1·82, 1·02 to 3·52). Conclusion: Perioperative intravenous fluid and weight thresholds were associated with postoperative adverse outcomes. These thresholds need independent validation. Graphical Abstract: Perioperative fluid thresholds and weight gain after colorectal laparoscopy were assessed for postoperative and respiratory complications and postoperative ileus. Thresholds for perioperative intravenous fluid administration were 3000 ml (area under the receiver operating characteristic (ROC) curve (AUROC) 0·63) for colonic and 4000 ml (AUROC 0·79) for rectal procedures. Postoperative weight gain of 2·5 kg was predictive of adverse outcomes (AUROC 0·77). Suggested thresholds need validation.